THE RELATIONSHIP BETWEEN ESSENTIAL SKILLS OF THE FUTURE OF WORK IN THE POST-COVID-19 ERA WITH THE PERFORMANCE OF SMEs ENTREPRENEURS IN THE NORTHEASTERN REGION - chaisena, Yupaporn; Phuworakij, Pensiri; Tinnarat, Ganyarat; Ploywilert, Walaiporn; Boonchom, Wanita (Journal of Liberal Arts and Management Science Kasetsart University, 2024)
The objective of this research was to test the relationship between the skills required for future work in the post-COVID-19 era with the performance of small and medium sized businesses in the manufacturing sector in the Northeast. This research was quantitative research. The sample group used in this research was 258 entrepreneurs using Taro Yamane's formula. The research instrument used to collect data was a questionnaire. Data was analyzed using multiple regression analysis. The research results found that Essential skills for the future of work in the post-COVID-19 era include 1) adaptability and flexibility, 2) creativity and innovation, 3) emotional intelligence, and 4) lifelong learning there was a relationship and a positive impact on the performance of SMEs businesses. Therefore, as a guideline for entrepreneurs or individuals who will become entrepreneurs in doing business in the post-COVID-19 era take necessary skills into consideration and develop your own skills appropriately for survival and business success. Entrepreneurs' preparation in terms of necessary skills for the future of work in the post-COVID-19 era was important for conducting business in the present.